1997
DOI: 10.1007/pl00000586
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal membrane stabilization by α-tocopherol against the damaging action of Vipera russelli venom phospholipase A2

Abstract: This investigation shows the membrane stabilizing effect of alpha-tocopherol against the damaging action of viper venom phospholipase A2 (PLA2). Liver lysosomal membranes from rats fed 100 mg and 200 mg alpha-tocopherol acetate per kilogram of diet were more resistant to damage by viper venom PLA2 compared with vitamin E-deficient rats. The membrane stabilizing effect of vitamin E is proposed to be due to the formation of a complex with the phospholipid hydrolysis products of the membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…These results are suggestive of siramesine-induced lipid peroxidation, because tocopherols, due to their lipophilic nature, are especially effective in protecting lipids from oxidation. It should, however, be noted that in addition to its function as an antioxidant, a-tocopherol has also been reported to inhibit protein kinase C and phospholipase A2, both possible mediators of cell death (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…These results are suggestive of siramesine-induced lipid peroxidation, because tocopherols, due to their lipophilic nature, are especially effective in protecting lipids from oxidation. It should, however, be noted that in addition to its function as an antioxidant, a-tocopherol has also been reported to inhibit protein kinase C and phospholipase A2, both possible mediators of cell death (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…TCDD was reported to disturb cell homeostasis, caused cell swelling and cell rupture (Pathak and Kundu, 2013 a, b). Similarly, intracellular increase in ions can elevate the prerequisite CPLA 2 , which is responsible for plasma and lysosomal destabilization (Mukherjee et al 1997). Further, it was reported that intracel-lular ions are able to increase intra-lysosomal pH, probably by interacting with membrane proton pump of the cell .…”
Section: Figmentioning
confidence: 99%
“…It has been suggested that the biochemical properties of PLA 2 enzymes, the availability of PC in a PLA 2 -sensitive membrane and/or various physicochemical properties of a cell membrane are the major factors that show the venom PLA 2 -induced membrane damage [7,9,25,47].…”
Section: Kinetic Parametersmentioning
confidence: 99%